2000
DOI: 10.1515/ijnsns.2000.1.4.305
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Differential Constraints for Analyzing Turbulence Models

Abstract: In this article we introduce a concept based on the differential constraints method to examine the closure procedure in Turbulence Models. We show how this concept may be applied to study the problem of interaction and mixing between two semi-infinite homogeneous turbulent flow fields of different scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…The results of this article continue our earlier studies of the problem of interaction and mixing between two semi-infinite turbulent flow fields of different scales given in [4,5] wherein it was proposed a concept based on the method of differential constraints [23,19] for examining the closure procedure for momentum equations in Parametric Turbulent Models. The key idea of this approach can be formulated shortly as follows: the algebraic expressions for the n-order moments of statistical characteristics of turbulent flow are determined as the equations of invariant sets (manifolds) of the corresponding differential equations.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The results of this article continue our earlier studies of the problem of interaction and mixing between two semi-infinite turbulent flow fields of different scales given in [4,5] wherein it was proposed a concept based on the method of differential constraints [23,19] for examining the closure procedure for momentum equations in Parametric Turbulent Models. The key idea of this approach can be formulated shortly as follows: the algebraic expressions for the n-order moments of statistical characteristics of turbulent flow are determined as the equations of invariant sets (manifolds) of the corresponding differential equations.…”
Section: Introductionsupporting
confidence: 78%
“…This implies existence of a solution to (4.4), (4.5). In [4] we proven this result directly for a problem of type (4.4), (4.5) and noted that this solution is essentially different from the well-known Barenblatt's solution [2].…”
Section: Stable Stratificationmentioning
confidence: 68%
See 1 more Smart Citation
“…it is assumed that the fifth-order cumulants are equal to zero. Therefore (see, [1], [24]), the following third-order mathematical model can be used Model 2:…”
Section: The Governing Equations To Modelmentioning
confidence: 99%
“…A concept of algebraic expressions for the n-order moments of statistical characteristics of turbulent flow as the equations of invariant manifolds of the corresponding transport equations enables us to examine the closure procedure for momentum equations. The invariant manifolds were used in [1], [2] for investigating the problem of the development of a shearless mixing layer in the third-order closure model wherein we showed that this approach may be used to obtain new reductions of the models under consideration and to construct a class of explicit solutions. Due to the differential constraints derived, it was established that the equation of the invariant manifold (differential constraints of the model) coincides with the classical tensor-invariant Hanjalic-Launder algebraic model of the triple correlations for an unstratified flow and with the Zeman-Lumley model for a stratified flow.…”
Section: Introductionmentioning
confidence: 99%